1982
DOI: 10.4141/cjps82-056
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Composition of Russian and Altai Wild Ryegrass and Crested Wheatgrass as Influenced by N Fertilization and Date of Harvest

Abstract: The effects of three rates of N fertilizer and nine fortnightly dates of initial harvest on the N, P, Ca, Mg and K concentrations and the K/(Ca + Mg) ratio of Russian wild ryegrass (Elymus junceus Fisch.), Altai wild ryegrass (Elymus angustus Trin.) and crested wheatgrass (Agropyron desertorum Fisch. Schult.) were studied on irrigated land for 2 yr. The N, P, K and K/(Ca + Mg) ratios declined with increasing maturity. The N, P, and K concentrations tended to increase with N fertilization, while N fertilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
12
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 9 publications
4
12
1
Order By: Relevance
“…Phosphorus concentrations of all grasses decreased with maturity (Table 3) and were within the range of other reports (Lawrence et al 1982;Currie et al 1986). Few significant differences in phosphorus content existed between species at each growth stage, but these differences became greater as the grasses matured.…”
Section: Phosphorussupporting
confidence: 70%
“…Phosphorus concentrations of all grasses decreased with maturity (Table 3) and were within the range of other reports (Lawrence et al 1982;Currie et al 1986). Few significant differences in phosphorus content existed between species at each growth stage, but these differences became greater as the grasses matured.…”
Section: Phosphorussupporting
confidence: 70%
“…Nutritionally relevant variation in mineral concentrations and KRAT have been also documented in crested wheatgrass (Agropyron cristatum and A. desertorum) (Asay et al 1996; and Russian wildrye (Psathyrostachys juncea) Asay and Mayland 1990;Jefferson et al 2001;Karn et al 2005). In comparisons with crested wheatgrass and Russian wildrye, Altai wildrye (Leymus angustus) had especially high KRAT values (Lawrence et al 1982). Despite the large number of studies of KRAT variation there has not been any effort to dissect the genetic control of various forage mineral concentrations at the genome level of grasses.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of K have been measured in Russian wildrye in Mayland (unpublished). Lawrence et al (1982) reported Russian wildrye had higher K/ (Mg+Ca) values than crested wheatgrass. They concluded that, particularly under heavy fertilization, supplementation of diets with Mg and/ or Ca might be required to prevent grass tetany and assure good performance.…”
mentioning
confidence: 99%